Weaning weight and compensatory growth in lambs from Ouled Djellal breed (Algeria) - Djellal F.; Mouhous A.; Kadi S.A.; Guermah H.; Madani T. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
As a leading supplier of red meat in Algeria, sheep are the only animals of high economic value to be able take advantage of pasture areas, especially in the steppe. Despite the existence of other breeds, sheep farming is dominated by the Ouled Djellal breed, which is well adapted to the conditions of the environment. Nevertheless, the low productivity contributes to an insufficient production of red meat and little scientific work is devoted to it. In a previous work, we showed that, in this breed, birth weight influences preweaning growth. In the present study, we propose to measure the influence of weight at weaning on growth and check the ability of this breed to catch up with growth (compensating growth). For this purpose, thirty Ouled Djellal lambs, born in autumn and weaned at four months of age, were divided into two lots of fifteen according to their weight. The average daily gain of the “skinny” lot was 158 ± 14 g and 139 ± 8 g for the two periods ranging from 120 to 150 and 120 to 210 days of age respectively. That of the “Normal” lot was 130 ± 13 g and 98 ± 9 g for the two periods ranging from 120 to 150 and 120 to 210 days of age respectively. The growth rate is statistically different (p = 0.002) between the two groups for the period 120-210 days of age. All the lambs were fattened for three months under almost similar conditions, especially feeding. At the end of the post-weaning growth period at the seventh month of age, the lambs weighed 29.1 ± 5.1 kg for the light group and 36.4 ± 4.1kg for the heavy group (p = 0.109). This would confirm the ability of this breed to adapt to rearing conditions by, for example, an appreciable compensatory growth. This will constitute an additional parameter of adaptation of this breed to the conditions, often unfavorable for breeding. Further studies are needed to confirm and quantify this compensatory growth.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)